TINJAUAN YURIDIS TENTANG PENINJAUAN KEMBALI DALAM PERKARA PIDANA PASCA PUTUSAN MAHKAMAH KONSTITUSI - Marius Gabriel Banurea (2022)
In Criminal Justice there are several legal remedies that can be taken if someone is not satisfied with the existing court decision, the legal remedies consist of ordinary legal remedies and extraordinary legal remedies. This research focuses on judicial review as an extraordinary legal remedy. The decision of the Constitutional Court Number 34/PUU-XI/2013 provides an opportunity to be able to carry out a review more than once, so there is the potential for legal uncertainty, because a case can have no end. In addition to the decision of the Constitutional Court that regulates requests for judicial review, there are several laws and regulations whose contents are contradictory to each other, thus potentially creating legal uncertainty for litigants in criminal justice. This research is a normative juridical research that provides an objective view of changes in the legal system and trial procedures from judicial review in criminal cases which are expected to truly create legal certainty for people who have litigation in criminal justice, but do not rule out the value of justice.